Wild to domestic and back again: the dynamics of fallow deer management in medieval England (c.11th-16th century AD) - Sykes, Naomi; Ayton, Gema; Bowen, Frazer; Baker, Karis; Baker, Polydora; Carden, Ruth F.; Dicken, Craig Arthur; Evans, Jane; Hoelzel, A. Rus; Higham, Thomas F.G.; Jones, Richard; Lamb, Angela L.; et al. (Taylor & Francis, 2016)
This paper presents the results of the first comprehensive scientific study of the fallow deer, a non-native species whose medieval-period introduction to Britain transformed the cultural landscape. It brings together data from traditional zooarchaeological analyses with those derived from new ageing techniques as well as the results of a programme of radiocarbon dating, multi-element isotope studies and genetic analyses. These new data are here integrated with historical and landscape evidence to examine changing patterns of fallow deer translocation and management in medieval England between the 11th and 16th century AD.